Counterterrorism prevention concept to support government policy in Indonesia - Bimantara, Angga; Supriyadi, Asep Adang (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Counter-terrorism strategies in Indonesia have evolved in response to the dynamic nature of global and domestic security threats. The Indonesian government has implemented a multifaceted approach, combining intelligence strengthening, law enforcement, deradicalization, socio-economic empowerment, and media and technology management. These efforts are critical to preventing the spread of radical ideologies and terrorist attacks. However, challenges such as human rights violations and coordination gaps remain, necessitating further examination of these strategies. Methods: This essay employs a literature review method with a qualitative descriptive approach. Data were collected from various secondary sources, including academic journals, government reports, books, and media articles. Relevant literature was sourced through keyword searches in academic databases. Thematic analysis was conducted to identify key themes related to Indonesia's counter-terrorism strategies, particularly in intelligence, law enforcement, deradicalization, and technology management. Findings: The analysis revealed that Indonesia’s counter-terrorism efforts are effective in certain areas, particularly intelligence collaboration between agencies like BIN, Polri, BNPT, and Densus 88. However, human rights concerns persist, particularly regarding the use of surveillance technologies and law enforcement practices. Deradicalization programs that integrate religious moderation and socio-economic empowerment show promise in reintegrating former terrorists into society. Additionally, big data and AI play an increasingly critical role in detecting online extremist content, though balancing privacy and security remains a challenge. Conclusion: Indonesia's counter-terrorism strategy demonstrates a comprehensive approach that addresses both immediate security concerns and long-term prevention of radicalization. While successful in many aspects, further improvements are needed to address human rights issues, enhance inter-agency coordination, and optimize the use of technology. A balanced approach that respects civil liberties while ensuring national security is essential for sustained success. Novelty/Originality of This Study: This study provides a detailed analysis of Indonesia's counter-terrorism strategies through a comprehensive literature review, highlighting the interplay between intelligence, law enforcement, social reintegration, and technology. It also emphasizes the importance of transparency and human rights in counter-terrorism efforts, which have received limited attention in previous studies.